THE INTERNET FOR EDUCATIONAL PURPOSES - Normuminova X.; Isaqulova Sh. (Western European Studies, 2024)
The global expansion of the Internet presents a multitude of opportunities for individuals worldwide. While students primarily engage with the Internet for socializing and entertainment, it is evident that it also serves as a valuable source of academic and scientific knowledge. Furthermore, the Internet enables access to current global news and a diverse array of information on topics ranging from hobbies to health. As such, it is essential to encourage students to harness this invaluable resource for academic pursuits. Hence, the Internet serves as a rapid means of disseminating information to a broad audience and transcending temporal and spatial constraints. Given this perspective, it is crucial to motivate students to utilize this invaluable resource for accessing any necessary information for their academic endeavors. Therefore, the objective of this research is to examine students' utilization of the Internet in their academic pursuits
Keywords: The Internet; Education; Academic Use of the Internet